Studi Literatur: Analisis Efektivitas Layanan Antar Obat Rumah Sakit - Agastyaning Dwi Ilma Binendra; Inge Dhamanti (Pusat Riset dan Inovasi Nasional, 2026)
Medication delivery services in hospitals represent a growing pharmaceutical innovation in Indonesia, particularly as a response to the COVID-19 pandemic and the increasing demand for efficient, patient-centered healthcare. This article is a literature review using a systematic approach that analyzes 15 scientific articles published in the last five years to evaluate the effectiveness of medication delivery services implemented in various hospitals across Indonesia. The findings indicate that these services have positively contributed to improving patient satisfaction, hospital pharmaceutical logistics efficiency, and treatment continuity, especially among patients with chronic conditions. However, several implementation challenges persist, including limited human resources, suboptimal integration of hospital information systems, and delays in reimbursement from the national health insurance (BPJS). Therefore, strengthening digital infrastructure, enhancing the capacity of pharmaceutical personnel, and ensuring sustainable healthcare financing policies are essential to support the long-term effectiveness of these services within hospital management systems.